Evaluasi Program Sistem Manajemen Sekolah Dasar Menggunakan Model Countenance Stake - triwiyanto, Teguh; Arafik, Muh; Pramono, Pramono; Nurabadi, Ahmad (Universitas Negeri Malang, 2023)
Abstract: The purpose of this study was to determine the evaluation of elementary school management programs using the Countenance Stake model. Quantitative approach is used in this research. The population of this study was the principals of district/city public elementary schools in East Java Province, totaling 1,323 people. The sampling technique used was cluster random sampling and simple random sampling, with a total of 290 people or 22 percent of the population. Data collection was carried out using a research instrument in the form of a questionnaire. Data analysis using path coefficient testing. The results showed that the strategic planning and financing management variables had a greater direct influence than the indirect influence through school culture and principal performance on school quality. Meanwhile, the variables of organizing, curriculum management, student management, education staff management, facility and infrastructure management, financing management, and community participation management have a greater indirect effect than the indirect effect through school culture and school principals' performance on school quality. Preparation (antecedents) as in the Countenance Stake model, has a direct influence on transactions and outcomes. Keywords: Program Evaluation, Elementary School Management, Countenance Stake Model. Abstrak: Tujuan penelitian ini untuk mengetahui evaluasi program manajemen sekolah dasar menggunakan model Countenance Stake. Pendekatan kuantitatif digunakan dalam penelitian ini. Populasi penelitian ini yaitu kepala sekolah dasar negeri kabupaten/kota Provinsi Jawa Timur yang berjumlah 1.323 orang. Teknik pengambilan sampel yang digunakan yaitu cluster random sampling dan simple random sampling, dengan jumlah 290 orang atau 22 persen dari populasi. Pengumpulan data dilakukan dengan menggunakan instrumen penelitian berbentuk angket. Analisis data menggunakan pengujian koefisien jalur. Hasil penelitian menunjukkan variabel strategi perencanaan dan manajemen pembiayaan memberikan pengaruh langsung lebih besar dibandingkan pengaruh tidak langsung melalui budaya sekolah dan kinerja kepala sekolah terhadap mutu sekolah. Sementara itu, variabel pengorganisasian, manajemen kurikulum, manajemen siswa, manajemen tenaga pendidikan, manajemen sarana dan prasarana, manajemen pembiayaan, dan manajemen partisipasi masyarakat memberikan pengaruh tidak langsung lebih besar dibandingkan pengaruh tidak langsung melalui budaya sekolah dan kinerja kepala sekolah terhadap mutu sekolah. Persiapan (antecedents) seperti dalam model Countenance Stake, memberikan pengaruh secara langsung terhadap transaksi dan hasil (outcome). Kata kunci: Evaluasi Program, Manajemen Sekolah Dasar, Model Countenance Stake.